Public opinion on cash transfers for children and adolescents in Guatemala: Overwhelming support for increased coverage and adequacy - Blofield, Merike (2023)
Child poverty is a multidimensional challenge and decades of evidence demostrate that cash transfer programs can provide simple and effective protection against poverty, especially extreme poverty. A nationally representative telephone survey conducted in Guatemala in May 2022 indicates very high support (88%) for a cash transfer program targeting children and adolescents. In addition, 90% are in favor of setting the value of the transfers to at least the basic food basket. Finally, a slight majority (almost 52%) supports extending the transfers to at least all children in poverty, while 46% support restricting the program to those in extreme poverty. Either way, given that the current program reaches only about 13 percent of children and adolescents in extreme poverty, there is broad support for a massive expansion in coverage.